THE INTENTION TO BECOME ENTREPRENEURS BETWEEN STUDENTS WHO LIVE WITH THEIR PARENTS AND STUDENTS WHO LIVE SEPARATE WITH THEIR PARENTS (CASE STUDY: STUDENTS AT FEB UNSRAT) - Patrick Kevin Giovani Gozalie; James Massie; Merinda Pandowo (Universitas Sam Ratulangi, 2023)
The various living arrangement options for college students who aspire to become entrepreneurs. It emphasizes the importance of creating an environment conducive to entrepreneurial pursuits and outlines potential solutions after graduations. This study aims to examine the effect of Students Who Live with their Parents and Students Who Live Separately with their Parents on Entrepreneurial Intention through Entrepreneurial Characteristics as an intervening variable. The population in this study were 100 students of the Faculty of Economics and Business, University of Sam Ratulangi Manado, in several study program from the Management, Accounting, and Development Economics. The sampling technique used in this study was Purposive Sampling while the data analysis used in this study was Path Analysis. The classic assumption test used in this study is the Normality Test, Multicollinearity Test and Heteroscedasticity Test. The results of this study prove that Students Who Live with Their Parents and Students Who Live Separate with their Parents has no positive influence on Entrepreneurial Intention, Students Who Live with their Parents has no positive influence on Entrepreneurial Characteristics while Students Who Live Separate with their Parents have positive influence on Entrepreneurial Characteristics, and Entrepreneurial Characteristics have a positive influence on Entrepreneurial Intention. Keywords: entrepreneurial intention, entrepreneurial characteristics